On the north equatorial current spatiotemporal modes and responses in the western boundary currents. (July 2022) - Li, Junlu; Gan, Jianping
Highlights: The NEC's intensity, migration, and bifurcation largely control the western boundary currents (WBCs) in the western North Pacific Ocean. The seasonality of the WBCs varies with the NEC's intensity while the effects of NEC's bifurcation and migration tends to offset each other. The study of the spatiotemporal modes in NEC-KC-MC provides a new understanding to the WBCs in the NEC-WBCs current system. Abstract: The North Equatorial Current (NEC) and western boundary currents (WBCs) of the Kuroshio Current (KC) and the Mindanao Current (MC) characterize the circulation pattern and water mass transports in the tropical western North Pacific. We utilized the validated three-dimensional and time-dependent China Sea Multi-scale Ocean Modeling System to investigate the variability of the WBCs and the physical processes linked with the upstream NEC and associated with the circulation. The latitude-dependent KC and MC strengthen downstream from the NEC bifurcation (NB) and are maintained by the northern and southern parts of the NEC, respectively. By effectively isolating the NEC spatiotemporal modes representing its intensity, meridional migration, and bifurcation location, we investigate the responses of the WBCs to the characteristics in an integrated NEC-WBCs current system. The NEC intensity peaks in spring and summer, while its bifurcation location strongly correlates with its migration. The southward (northward) NEC migration during early spring (late autumn) feeds more NEC waters to the MC (KC). Yet, the simultaneous southward (northward) shifting NB distributes more NEC waters to the KC (MC) and offset the contribution of the migration. Thus, the intensity of the KC (MC) is primarily controlled by the NEC intensity, reaching the maximum during spring (summer). The specific water masses such as the North Pacific Tropical Water and the Equatorial Surface Water, are bounded by the time-dependent NB, distributing northward and southward respectively through the WBCs. By resolving spatiotemporal modes in NEC-KC-MC, the study provides a new understanding to the WBCs in the NEC-WBCs current system.